The dichotomous role of epiregulin in pain. Issue 5 (May 2020) - Verma, Vivek; Khoury, Samar; Parisien, Marc; Cho, Chulmin; Maixner, William; Martin, Loren J.; Diatchenko, Luda
Abstract : Abstract: It has recently been shown that epidermal growth factor receptor (EGFR) contributes to the pathogenesis of pain. We scanned genetic markers within genes coding for receptors of the EGFR family (EGFR, ERBB2, ERBB3, and ERBB4) and their ligands (AREG, BTC, EGF, EPGN, EREG, HBEGF, MUC4, NRG1, NRG2, NRG3, NRG4, and TGFA) for association with self-reported pain intensity in patients with chronic facial pain who participated in the Orofacial Pain: Prospective Evaluation and Risk Assessment (OPPERA) cohort. We found that only epiregulin (EREG) was associated with pain. The strongest effect was observed for a minor allele at rs6836436 in EREG, which was associated with lower chronic pain intensity. However, the same allele was associated with higher facial pain intensity among cases with recent onset of facial pain. Similar trends were observed in an independent cohort of UK Biobank (UKB) where the minor allele at rs6836436 was associated with a higher number of acute pain sites but a lower number of chronic pain sites. Expression quantitative trait loci analyses established rs6836436 as a loss-of-function variant of EREG. Finally, we investigated the functional role of EREG using mouse models of chronic and acute pain. Injecting mice with an EREG monoclonal antibody reversed established mechanosensitivity in the complete Freund's adjuvant and spared nerve injury models of chronic pain. However, the EREG monoclonal antibody prolonged allodynia when administered during the development of complete Freund's adjuvant–induced mechanosensitivity and enhanced pain behavior in the capsaicin model of acute pain. Abstract : Supplemental Digital Content is Available in the Text.We identified dichotomous role of epiregulin in the pathophysiology of pain. It is analgesic during the early stages while pronociceptive in establishing pain.